The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ijc.1349.abs
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of hepatocyte growth factor activator inhibitor type‐2/placental bikunin (HAI‐2/PB) in human glioblastomas: Implication for anti‐invasive role of HAI‐2/PB in glioblastoma cells

Abstract: Hepatocyte growth factor activator inhibitor type-2/placental bikunin (HAI-2/PB) is a serine proteinase inhibitor that contains 2 Kunitz-domains and a presumed transmembrane domain. It has broad inhibitory spectra against various serine proteinases showing potent inhibitory activities not only to hepatocyte growth factor activator but also to plasmin, trypsin and kallikreins. In this study, we investigated the expression of HAI-2/PB in human gliomas in viv o and the effects of HAI-2/PB on the fibrinolytic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 11 publications
(14 reference statements)
3
27
0
1
Order By: Relevance
“…Primers were designed using the program PrimerQuest (www.idtdna.com) or primer 3, unless otherwise stated. Primer sequences and lengths of products were: G3PDH-F, GTGAAGGTCGGAG TCAACGGA; G3PDH-3, GGTGAAGACGCCAGTGGACTC (300 bp) (20); Wnt10B-5, GCCATCCTCAAGCGCGGTTTC; Wnt10B-3, GAATCCAAGAAATCCCGAGAG (326 bp) (21); Wnt10B probe, CTGTGGCTGGAAGGGCAGTG; Wnt5AF, GGGGAAATGTGGTTTAATGGTG; and Wnt5AR, AAAT GGAGGTTGGAGACAAAGG (368 bp).…”
Section: Quantitative Real-time Pcr (Q-pcr)mentioning
confidence: 99%
“…Primers were designed using the program PrimerQuest (www.idtdna.com) or primer 3, unless otherwise stated. Primer sequences and lengths of products were: G3PDH-F, GTGAAGGTCGGAG TCAACGGA; G3PDH-3, GGTGAAGACGCCAGTGGACTC (300 bp) (20); Wnt10B-5, GCCATCCTCAAGCGCGGTTTC; Wnt10B-3, GAATCCAAGAAATCCCGAGAG (326 bp) (21); Wnt10B probe, CTGTGGCTGGAAGGGCAGTG; Wnt5AF, GGGGAAATGTGGTTTAATGGTG; and Wnt5AR, AAAT GGAGGTTGGAGACAAAGG (368 bp).…”
Section: Quantitative Real-time Pcr (Q-pcr)mentioning
confidence: 99%
“…This indicates an exclusive role for ITI H2 in the control of cell invasion that is independent from bikunin. In addition to the invasion assays used here, bikunin has also been previously examined in glioma cell migration models where transient overexpression of placental bikunin alone did not significantly affect migration despite an inverse correlation of primary tumor mRNA levels with malignancy (23). Therefore, it is reasonable to assume that the ITI H2 isolated and identified in our purified fractions is individually responsible for the inhibitory effects on glioma cell invasion rather than the covalently bound bikunin.…”
Section: Discussionmentioning
confidence: 96%
“…[15][16][17]19,25,39 Previous study has shown that KD-1 was the major functional domain in HAI-2 in inhibiting the activity of its target proteases in vitro. 6 However, the roles of the 2 KDs of HAI-2 in tumour suppressive functions have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] HAI-2 has been found to be underexpressed in several types of cancers such as breast cancer, 14 renal-cell carcinoma, 15,16 and glioblastoma. 17,18 Ectopic expression of HAI-2 was able to suppress tumour cell growth in vitro in renal-cell carcinoma 16 and inhibit cell migration and/or invasion in breast and renal-cell carcinoma. 16,19 However, the roles of HAI-2 in human HCC have not been fully characterised.…”
mentioning
confidence: 99%